SUBALTERN RESPONSES TO EPISTEMIC VIOLENCE; THE LEGACY OF COLONIALISM (The Pretoria Student Law Review, 2021)
Epistemic violence is the extent in which local knowledge has been ignored, rejected and in some cases completely wiped out.2 It stems from a constant repression that imposes mental violence rather than physical violence. This cognitive abuse is instigated and institutionalised by a coloniser, who sees himself as superior and limits the ‘subordinate’s’ happiness by burdening their knowledge of freedom.3 This field of violence is portrayed throughout South African history, which is commonly signified by the arrival of Jan Van Riebeek in the Cape of Good Hope. Vale is perpetually mesmerised by the nature in which ideas, as a result of this, were carried from different corners of the world into South Africa, but in stark contrast, that very same South Africa is now often portrayed as a ‘one-dimensional South Africa’ as a result of epistemic violence.4 In order to redress the past and contribute to epistemic diversity and justice, one must have a sufficient grasp of the systemic integration of western knowledge into South Africa, and this serves as a direct example of epistemic violence. The real questions that must be asked are; first, how Western intellectual history has contributed to epistemic violence in South Africa, for example through positivism, which removed morality from law and therefore instilled the oppression of the apartheid regime; second, how we may make use of some parts of this intellectual history to respond to epistemic violence, for example, by using Black Consciousness to advocate for epistemic diversity.5 This essay aims to use critical jurisprudence as a tool to listen to the different voices and perspectives excluded by the traditional mainstream, without assimilating them. It also aims to engage with and reflect on the abovementioned theme of epistemic violence, and reflect on how critical legal theories could assist in the development of a critical jurisprudence. It will draw inspiration from SleeperBlack, an artwork by William Kentridge showing the discomfort of ignorance.
Keywords: Epistemic violence; critical jurisprudence; epistemic diversity and justice; integration of western knowledge